Legal Policy On The Existence Of Criminal Law Of Illegal Foreign Labor In Indonesia - I Dewa Putu Gede Anom Danujaya; Sri Endah Wahyuningish (Jurnal Daulat Hukum, 2019)
The problems that arise in connection with the use of foreign labor in Indonesia, is a violation of residence permit and work permit. In the passport and foreign workers have written that the Indonesian government granted permission by the immigration authorities is to work as migrant workers in Indonesia with a position and a certain time even just as a tourist. Not infrequently the user companies often hide these illegal foreign workers. Indonesia is a country of law where any problems exist in the country has been governed settlement conditions in the form of the rule of law. In matters of illegal foreign workers in Indonesia the rules governing such example Act No. 13 of 2003 on employment has made a policy both administrative and criminal policy. Criminal in the world of employment can not be denied as a punishment to provide a deterrent effect, especially entrepreneurs form of a corporation in the use of illegal foreign labor. Labor gives a great influence in the development of national economy and the arrival of foreign workers into Indonesia when no restrictions are adjusted will cause social unrest, economic, and human resources are poor in Indonesia. Criminal policy has been implemented on the rules governing the use of foreign labor in Indonesia. Labor gives a great influence in the development of national economy and the arrival of foreign workers into Indonesia when no restrictions are adjusted will cause social unrest, economic, and human resources are poor in Indonesia. Criminal policy has been implemented on the rules governing the use of foreign labor in Indonesia. Labor gives a great influence in the development of national economy and the arrival of foreign workers into Indonesia when no restrictions are adjusted will cause social unrest, economic, and human resources are poor in Indonesia. Criminal policy has been implemented on the rules governing the use of foreign labor in Indonesia. Keywords: Foreign Workers; Illegal; Criminal Policy.